Uji Toksisitas Sub-Kronik 28 Hari Ekstrak Metanolik Daun Benalu Teh Dan Benalu Mangga Terhadap Fungsi Jantung Tikus Wistar Betina - M. Abdul Qodir Jailani; Nour Athiroh Abdoes Sjakoer; Nurul Jadid Mubarakati (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2022)
Benchmark damage to heart function lies in LDH, CPK, CK-MB as well as histopathology of heart organs. This study aims to determine the 28-day subchronic toxicity of methanolic extracts of tea parasites and mango parasites (EMBTBM) on the heart function of female Wistar rats by experimental methods. In analyzing the data, one way ANOVA test is used, namely SPSS with version 1.0 1.0. A total of 20 female Wistar rats were used as test animals. Then divided into 4 treatments, namely control, treatment 1 dose 250 mg/KgBW, treatment 2 dose 500 mg/KgBW and treatment 3 dose 1000 mg/KgBW, each containing 5 mice. From the results of the study, it was found that EMBTBM positively contained flavonoids in the form of quercetin and rutin to reduce LDH, CPK, and CK-MB levels in female Wistar rats, and be safe against the histopathology of the heart organs of female Wistar rats.